Risk factors and clinical outcomes of candidaemia in patients treated for Clostridium difficile infection. (May 2015) - Russo, A.; Falcone, M.; Fantoni, M.; Murri, R.; Masucci, L.; Carfagna, P.; Ghezzi, M.C.; Posteraro, B.; Sanguinetti, M.; Venditti, M.
Abstract: The alterations occurring in the intestinal flora during Clostridium difficile infection (CDI) may promote the translocation of Candida to the blood and the development of candidaemia. The aim of our study was to analyse clinical findings of these patients to determine the risk factors associated with the development of candidaemia subsequent to CDI. We compared 35 patients with candidaemia subsequent to CDI with 105 patients with CDI. Patients with candidaemia showed more severe infections and higher mortality. The ribotype 027 strain and vancomycin treatment at ≥1000 mg/day were prevalent in patients developing candidaemia. CDI may predispose to the translocation of Candida .